Perception of Marital Satisfaction Among Couples in the Asante Akim North Area - Amoah, Charles Agyei; Agyemang, Thomas; Agyemang, Samuel; Sekyi, John Richmond (International Journal of Scientific Research and Management (IJSRM), 2020)
The purpose of the study was to investigate the perception couple holds that may knit marriages together in order to avert many crises that are common in marriages in the Asante Akim North Area. Two research questions and two hypotheses were formulated to guide the study. The survey design which involves the qualitative and quantitative approach was employed for the study. The simple random sampling technique was used to select a sample size of 200 respondents (thus 100 males and 100 female couples) for the study. The study sought the views of respondents using questionnaires and focus group interview was the main instrument used for the study. Data were analyzed using various analytical techniques and t-tests. Among the present study’s findings was that there was no statistically significant sex difference in what constitute marital satisfaction. The findings also suggested that there was no statistically significant age difference in what constitute marital satisfaction.The study concluded that; intimacy in a relationship is very important particularly with reference to how we spend our time. A lot of the frictions that do come into marriages are as a result of lack of spending time together during leisure time. Couples that had fun together during leisure time were found to be more satisfied in their marriages. It was recommended that, there is the need for effective Guidance and Counselling service concerning home management and financial management on the part of couples and also newly married, aspirants and the youth should seek counselling about marriage, concerning joys and problems.